Penerapan Pola Desain untuk Perancangan Aplikasi Stasiun Cuaca Nirkabel - Lintang Dwi Febridiani (Pusat Penelitian Informatika - LIPI, 2012)
One of the problems in object oriented application development is how to achieve a good quality software design. This paper presents a good quality software design for wireless weather system application based on design patterns. Abstract Factory and Mediator design patterns are used to design the application based on problem similarity. Design process produces a static and a dynamic model of the application in UML (Unified Modeling Language) diagrams. We use class cohesion and coupling metrices to measure the quality of our design. Measurements show our proposed design has high class cohesion and low class coupling.